Awareness of Digital Content in the Electronic Gadget Industry: A Demographic Study from Himachal Pradesh - Singh, Kuldeep; Chanda, Kiran (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The study "Assessing Awareness of Digital Content in the Electronic Gadget Industry: A Demographic Study from Himachal Pradesh" explores how digital content marketing is becoming more and more important as a tactical tool for customer interaction. Effective targeting requires a grasp of content awareness across demographics as digital platforms change the way businesses engage with viewers. With an emphasis on how consumer awareness differs depending on demographic characteristics, including age, gender, education, occupation, and city, this study investigates consumer awareness of eleven digital content formats employed by the electronic device sector. A systematic questionnaire was used to gather information from 472 respondents spread across four cities in Himachal Pradesh. The content kinds were ranked according to awareness levels using Dichotomy analysis which showed that respondents were most aware of online videos, followed by blog posts and articles, social media posts, webinars and live streams, podcasts, influencer content, paid advertisements, Product reviews and Comparison website, interactive content, infographics, and user-generated content, which they were least aware of. Preferences were evaluated using the Kruskal-Wallis H test. Except for interactive content and product reviews & comparison websites, where group variance was statistically significant, the Kruskal-Wallis H test revealed no discernible differences in awareness across the majority of demographic categories. The study provides information for urban India's audience-specific content strategy.